Parameter identification for a three-dimensional aerofoil system considering uncertainty by an enhanced Jaya algorithm. Issue 3 (4th March 2022) - Ding, Z. H.; Lu, Z. R.; Chen, F. X.
Abstract : Parameter identification for an aerofoil with an external store system based on an enhanced Jaya algorithm is proposed. The discrepancy between the measured and calculated displacement responses is used to formulate the objective function, which will be optimized by the enhanced Jaya algorithm. In the enhanced Jaya algorithm, two variants are introduced: the k -means clustering is employed to utilize the colony information fully; and a new updating equation that focuses on the exploration search is designed for the best-so-far solution in each cycle. During the identification process, both the inherent and extrinsic uncertainties existing in the aerofoil system are considered. The final identification results show that owing to its strong global search ability and robustness, the proposed enhanced Jaya can clearly identify the aerofoil system, even when the system is under quasi-periodic oscillations. The identification accuracy is better than that acquired by other approaches.